1998
DOI: 10.1038/sj.onc.1201966
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of cell cycle regulatory proteins expression in transgenic models of thyroid tumours

Abstract: Cell cycle proteins regulate the transitions from G1 to S and G2 to M phases. In higher eukaryotes, their function is controlled by intracellular cascades regulated by extracellular growth factors. We have studied in previously described transgenic mouse models for thyroid proliferative diseases the expression of the key proteins regulating the cell cycle by Western blotting and immunohistochemistry, and have correlated the observations with the known actions of the transgenes on the signal transduction cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…p27 is expressed at high levels in normal thyrocytes both in vitro (this study) and in the intact thyroid gland, in both human (17,40,60) and mouse (13). Many studies suggest that p27 plays a role in growth arrest accompanying differentiation (16,49,72), and p27-null mice exhibit hyperplasia of many highly differentiated cell populations, including endocrine glands (19,33,47) (although thyroid was not specifically studied).…”
Section: Discussionmentioning
confidence: 99%
“…p27 is expressed at high levels in normal thyrocytes both in vitro (this study) and in the intact thyroid gland, in both human (17,40,60) and mouse (13). Many studies suggest that p27 plays a role in growth arrest accompanying differentiation (16,49,72), and p27-null mice exhibit hyperplasia of many highly differentiated cell populations, including endocrine glands (19,33,47) (although thyroid was not specifically studied).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that cyclin D3 is the predominant cyclin D expressed in quiescent thyrocytes of primary cultures of dog tissue , and of mice in vivo (Coppee et al, 1998). In dog thyrocytes, TSH (cAMP), unlike all the other known mitogenic factors, does not induce the accumulation of cyclins D , but stimulates the expression of p27 kip1 (Depoortere et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…14,15,48 Coexpression of both transgenes enhanced tumorigenesis. In a mouse model of Carney complex tumor syndrome, a disease involving multiple endocrine and non-endocrine neoplasms, heterozygous knockout of the R1A regulatory subunit of protein kinase A led to papillary thyroid carcinoma development in 5 out of 44 mice.…”
Section: Other Modelsmentioning
confidence: 99%